1988
DOI: 10.1021/ic00292a007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the formation of FeII(edta)NO in the system FeII(edta)/NO/HONO/NO2- in aqueous solutions

Abstract: NO, HONO, and N02" react with Fen(edta) in aqueous solution to produce Fen(edta)NO. The reaction with NO is too fast for conventional stopped-flow and -jump techniques, whereas the reaction with H0N0/N02" can be followed kinetically by using stopped-flow techniques. This reaction occurs in two parallel paths of different order, viz. pseudo first and pseudo zero order in Fen(edta) concentration, respectively. The contribution of each path strongly depends on the pH and total nitrite concentration employed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 1 publication
6
19
0
1
Order By: Relevance
“…For example, the oxidation kinetics of [Fe II (edta)] with molecular oxygen showed the same pH dependence. [21,22] But, moreover, kinetic studies of the reaction of [Fe II (edta)] with HONO or NO 2 Ϫ also showed the same pH dependence, [35,36] which supports our suggestion that the observed bell-shaped curves are due to the distribution of species in solution and not due to an acid-catalyzed process, as suggested in an earlier study. [21] [Fe II (cdta)] fitted with three exponential functions.…”
Section: Kinetic Measurementssupporting
confidence: 88%
“…For example, the oxidation kinetics of [Fe II (edta)] with molecular oxygen showed the same pH dependence. [21,22] But, moreover, kinetic studies of the reaction of [Fe II (edta)] with HONO or NO 2 Ϫ also showed the same pH dependence, [35,36] which supports our suggestion that the observed bell-shaped curves are due to the distribution of species in solution and not due to an acid-catalyzed process, as suggested in an earlier study. [21] [Fe II (cdta)] fitted with three exponential functions.…”
Section: Kinetic Measurementssupporting
confidence: 88%
“…As Zang et al . () showed that reaction rates increased at lower pH, similar experiments were carried out at pH 6.5 and 7.5. In experiments with ca.…”
Section: Resultssupporting
confidence: 59%
“…Zang et al . () showed that the reaction of Fe(II)‐EDTA under anoxic conditions with an excess of nitrite produces Fe(III)‐EDTA and Fe(II)‐EDTA‐NO in a 1:1 ratio (equation ). 2[Fe(II)‐EDTA]2+NO2+2normalH+[Fe(II)‐EDTA‐NO]2+Fe(III)‐EDTA+normalH2O…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Known intracellular targets include enzymes containing haem and Fe-S centres, such as guanylate cyclase [33] and lipoxygenase [34]. NO' also forms stable complexes with inorganic iron [35], and relatively stable nitrosothiols and nitrosamines on proteins [36, 371. Any of these events might influence oxidative events either in the medium or within the cells. We are presently investigating these possibilities.…”
Section: +Pmamentioning
confidence: 99%